Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Find the inverse function f^-1(x) for the one-to-one function?
f(x)=2/x+3
2 Answers
- ?Lv 79 years agoFavorite Answer
I am assuming that f(x) = 2/(x + 3).
In order to find the inverse of a function, let f(x) = y, interchange x and y, and re-solve for y; the resulting function will be the inverse function.
So, letting f(x) = y gives:
y = 2/(x + 3).
Then, interchanging x and y:
x = 2/(y + 3).
Re-solving for y:
x(y + 3) = 2 ==> y = 2/x - 3.
Therefore, f^-1(x) = 2/x - 3.
I hope this helps!
- Anonymous9 years ago
Let y = 2/(x+3)
=> Interchanging y and x:
=> x = 2/(y+3)
=> 2/x = y+3
=> (2/x) - 3 = y
Thus f^-1(x) = (2/x) - 3
Source(s): A Level Math Student